Significance of type II fiber atrophy in chronic alcoholic myopathy - Fernández-Solá, Joaquim; Sacanella, Emilio; Estruch, Ramón; Nicolás, Josep-Maria; Grau, Josep-Maria; Urbano-Márquez, Alvaro (Journal of the neurological sciences, 1995)
To determine the significance of type II fiber atrophy in alcoholic myopathy and its relationship with ethanol-related diseases a prospective study was carried out in 100 chronic alcoholics who showed clinical suspicion of skeletal myopathy. Measurement of muscle strength, laboratory analysis, nutritional assessment and open biopsy of deltoid muscle were performed in each case, as well as electrophysiological testing for peripheral neuropathy. Hepatic ultrasonography and liver biopsy, echocardiography and radionuclide cardiac scanning were carried out in selected subjects. According to histomorphometric analysis, type II fiber atrophy was found in 33 cases (33%), being selective for type II B fiber in 23 (70%). Skeletal myopathy was diagnosed in 61 cases, alcoholic cardiomyopathy in 26, peripheral neuropathy in 23 and cirrhosis in 12. Patients with type II fiber atrophy had a significantly higher total lifetime dose of ethanol, presented a greater incidence of skeletal myopathy and peripheral neuropathy, and exhibited significantly lower values of percentage of ideal body weight and lean body mass than their counterparts. However, the only independent factors for developing type II fiber atrophy were the coexistence of caloric malnutrition ( p = 0.004) and the presence of skeletal myopathy ( p = 0.043). Selective type II fiber atrophy is a non-specific finding in alcohol-induced muscle damage appearing, overall, in the patients with caloric malnutrition as well as in those with histologic evidence of myopathy.